Introducing occupational health management in the German Armed Forces. (3rd July 2017) - Latza, Ute; Hampel, Eva; Wiencke, Markus; Prigge, Michaela; Schlattmann, Andreas; Sommer, Sabine
Summary: Holistic approaches to workplace health promotion (WHP) within the military setting are challenging. In 2015, the German Ministry of Defense initiated a 6-month pilot study of WHP in the Federal Armed Forces. The pilot study was to identify organizational challenges that should be addressed before the Ministry implemented a comprehensive occupational health management policy in all departments. Eleven diverse departments were selected to participate in a WHP program that addressed physical activity, diet, stress management and addiction prevention. As part of the evaluation concept, we interviewed coordinators, and department heads focusing on transfer factors from the perspective of the implementers. All coordinators and their department heads or deputies participated in semi-structured face-to-face on-site interviews. The data were analyzed based on qualitative content analysis. The coordinators (officers with sports science degree) seemed fully prepared and capable to master the new task. They experienced difficulties in adapting WHP activities to local structures and needs, and complications in administering modular activities. Department heads described conflict regarding human resources between the military mission and the implementation of WHP. Commitment to WHP was a strong facilitator. The interviews identified various barriers related to support by middle management (supervisors) and specific work conditions (e.g. shift work). If occupational health management is to be successfully implemented on a large scale, conceptional and practically collaboration is necessary between WHP and occupational safety and health, and organization and leadership, respectively. Supervisors will benefit from open communication about compensation for the release time of their subordinates to attend WHP.